A new strategic approach of fuzzy–quality function deployment and analytical hierarchy process in construction industry. Issue 2 (1st January 2015) - Raut, Rakesh D.; Mahajan, Vaishali C.
This paper aims to develop an integrated multi–criteria decision making (MCDM) analytical tool, combining fuzzy–quality function deployment (F–QFD) and analytic hierarchy process (AHP) approach for preference, in order to examine and to determine the best residential housing project in India. A new approach, fuzzy–QFD–AHP (FQA) MCDM method, has been suggested to combine the results of these techniques to find the final ranking. This paper integrates F–QFD and AHP; AHP is used to obtain the relative importance of the evaluation criteria. The fuzzy–QFD approach typical for residential house selection in the house of quality (HOQ) is used in determining the importance weights for the customer requirements. Utilising the linguistic factor to organise criteria and sub–criteria weight, fuzzy set are pair wise compared with fuzzy QFD and solved by a proposed fuzzy suitability index (FSI). The case study findings demonstrated that the FQA MCDM model could be successfully applied in the housing projects as a strategic tool to facilitate marketing decisions. A team has been formed to collect and verify the expectations of the customer profile of the sample project, which was a high–rise building project located in Mumbai, India.